Methylmercury content in soil and litter from the Amazonian rainforest and its potential fate during forest fires - Fostier, Anne Helene; Amouroux, David; Tessier, Emmanuel; Viana, José Lucas Martins; Richter, Larissa (Frontiers in Environmental Chemistry, 2023)
Methylmercury in soils and vegetation from the Amazonian rainforest has still been poorly studied.The aim of this work was then to determine total [THg] and methylmercury [MeHg] concentrations in litter and surface soil, MeHg deposition by litterfall and MeHg fate during a forest fire in the Amazonian rainforest. Samplings of litter, soil (0-1, 1-2, 2-5 cm) and ash were carried out before (BB) and after (AB) a prescribed forest fire. The results showed a low [THg] (34 ± 8 ng g -1 ) and[MeHg] (0.16 ± 0.03 ng g -1 ) in litter, with a corresponding low estimated MeHg litterfall flux (0.13 ± 0.03 µg m -2 yr -1 . But it was highlighted that the experimental design may have resulted in some loss of Hg and consequently to an underestimation of the initial net THg and MeHg depositions.In ashes, [THg] and [MeHg] were 23 ± 8 ng g -1 and 0.11 ± 0.04 ng g -1 , respectively. Although a significant part of Hg contained in biomass was lost during the fire, the [MeHg]/[THg] ratio was not affected by it and was the same in litterfall and ash ( 0.5%).In soil, average [THg] BB was 149 ± 12 ng g -1 in the three layers and [MeHg] was between 0.8 and 1.0 ng g -1 . The forest fire only affected the superficial soil, with a significant decrease of [THg] and [MeHg] in the 0 -1 layer. Similarly, the decrease of the [MeHg]/[THg] ratio in the surface soil layer suggested that MeHg was more readily emitted or degraded than other Hg species present.